Simulation of the MARA 10 test representing a core disruptive accident - Robbe, Marie-France; Lepareux, Michel; Casadei, Folco (Computer Assisted Methods in Engineering and Science, 2022)
In the case of a Hypothetical Core Disruptive Accident in a Liquid Metal Fast Breeder Reactor, the core of the nuclear reactor is assumed to have partially melted, and the interaction between molten fuel and liquid sodium creates a high-pressure gas bubble in the core. The violent expansion of this bubble loads and deforms the reactor vessel and the internal structures, thus endangering the safety of the nuclear plant. The MARA 10 experimental test simulates a HCDA in a l/30-scale mock-up schematising simply a reactor block. The vessel is filled with water, topped with an air blanket. The test is fired using an explosive charge. This paper presents the numerical models implemented in the EUROPLEXUS code, and a numerical simulation of the test. The evolution of the fluid flows and the deformations of structures are analysed in detail to understand the progress of the explosive phenomenon.